Dynamics and Challenges of Implementing the Concepts of Green Economy and Blue Economy in Facing Climate Change in Indonesia - Enno Haya Gladya Naranta (Universitas Muhammadiyah Surakarta, 2024)
Introduction: This research investigates the impact of climate change in Indonesia, particularly concerning the policy on the export of sea sand regulated by Government Regulation Number 26 of 2023. Utilizing a literature review and document analysis method, the study reveals the interconnection of international and national legal norms with climate change and its effects on vital sectors. Methodology: The research stands out for its interdisciplinary approach, exploring the implications of climate change on sectors such as agriculture, fisheries, and the consequences of natural disasters. Discussion: The analysis of the sea sand export policy highlights potential environmental damage and non-compliance with sustainable economic principles,becoming a primary focus in the global context of climate change. Conclusion: Concluding that a reevaluation of the sea sand export policy is needed from the perspective of climate change and environmental protection, the research offers legal recommendations to strengthen sustainability aspects.